Ethics, Politics and Migration: Public Debates on the Free Movement of Romanians and Bulgarians in the UK, 2006–2013. (February 2016) - Balch, Alex; Balabanova, Ekaterina
Public debates on immigration have become the subject of much concern, particularly in the UK. This article applies an ethical lens to assess changes in public debates over intra-EU migration in six UK national newspapers during 2006 and 2013. It finds an almost complete dominance of communitarian justifications, mainly based on welfare chauvinism, but a notable increase in security-related arguments and a decrease in economic nationalist ideas. Alternative cosmopolitan arguments about immigration go from rare to virtually absent. The discussion links these shifts to a failure of the UK centre-left to overcome historic difficulties in presenting a coherent narrative on immigration policy.